Donor thyroid hormone therapy is associated with an increased risk of graft dysfunction after heart transplantation. Issue 7 (24th May 2020) - Peled, Yael; Lavee, Jacob; Kassif, Yigal; Arad, Michael; Kogan, Alexander; Peled, Amir; Tirosh, Amir; Sternik, Leonid; Ram, Eilon
Abstract: Objective: Heart transplantation (HT) is uniquely associated with the potential impact of thyroid hormone therapy at three intersecting levels—donor, operation, and recipient. We aimed to study the effect of thyroid hormone therapy of the donor on primary graft dysfunction (PGD). Methods: A retrospective cohort study was conducted on 209 HT recipients assessed from 1997 to 2018; for 33 of the recipients, the donors had received T4 (DT4 group), and for 176, the donors had not (NoDT4 group). The primary endpoint was PGD defined according to the International Society for Heart and Lung consensus statement. Results: Both the incidence (58% vs 35%, P = .022) and the severity of PGD (42% vs 25% moderate/severe, P = .007) were significantly higher in the DT4 recipients. Multivariable analysis showed donor T4 therapy to be independently associated with a 3.5‐fold increased risk for PGD (OR = 3.44, 95% CI 1.26‐9.86). These results remained consistent after propensity score analysis. Conclusions: Donor thyroid hormone therapy is independently associated with an increased risk of PGD. Hypothesizing a "withdrawal effect" as the cause, we suggest that administration of thyroid hormone to the recipient at time of reperfusion could counter this negative effect. Prospective studies are needed to validate this hypothesis‐generating study.